Emissions trading, CDM, JI, and more: The climate strategy of the EU - Gernot Klepper; Sonja Peterson (Fondazione Eni Enrico Mattei (FEEM), 2005)
The objective of this paper is to assess the likely allocation effects of the current climate protection strategy as it is laid out in the National Allocation Plans (NAPs) for the European Emissions Trading Scheme (ETS). The multi-regional, multi-sectoral CGEmodel DART is used to simulate the effects of the current policies in the year 2012 when the Kyoto targets need to be met. Different scenarios are simulated in order to highlight the effects of the grandfathering of permits to energy-intensive installations, the use of the project-based mechanisms (CDM and JI), and the restriction imposed by the supplementarity criterion.
Keywords: Q48; D58; Q54; F18; 330; EU; EU emissions trading scheme; National allocation plans; CDM and JI; Computable general equilibrium model; DART; Kyoto targets; Klimaschutz; Allokation; Joint Implementation; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; EU-Staaten